AB0415 A New Prognostic Factor to Sustain Remission for 2 Years after Adalimumab Discontinuation & the Clinical Outcomes in RA Patients: Honor Study 2-Years Results. (10th June 2014) - Tanaka, Y.; Hirata, S.; Kubo, S.; Fukuyo, S.; Hanami, K.; Sawamukai, N.; Nakano, K.; Nakayamada, S.; Yamaoka, K.; Saito, K.
Abstract : Background: Discontinuation of biologics without flaring in RA patients is our next treatment goal, which contributes to reduce economic burden and safety risk such as infections. There are some reports of biologic free status, but the long term evidence is just getting underway. Objectives: To compare continuing and discontinuing adalimumab (ADA) for 2 years without flaring, and to identify factors enabling established patients with RA to remain ADA-free. Methods: Of 197 RA patients treated with ADA + methotrexate (MTX); their mean DAS28-ESR score was 5.4, mean disease duration was 8.9 years and mean age was 60.7 years at baseline, 75 patients who met the ADA-free criteria (steroid-free and sustained DAS28-ESR remission for 6 months with stable MTX doses) were divided into 2 groups, ADA discontinuation (ADA-free) group and ADA continuation group based on shared decisions between patients and rheumatologists, and studied for 2 year. Univariate and multivariate logistic regression analysis were performed to identify prognostic factors to sustain remission for 2 years after ADA discontinuation, and ROC analysis was conducted to determine the cut-off values for high estimation of sustained remission, using the factors identified by logistic regression analysis. Results: There was no significant difference in the patients' backgrounds between ADA discontinuation group (n=47) and continuation group (n=15) except MMP-3 values (230 vs 297 ng/mL, respectively). At 2-years after ADA discontinuation or continuation decision was made, the DAS28-ESR remission rate was 36% in the ADA continuation group and 67% in the continuation group ( P =0.0706 ). DAS28-ESR and age at the study entry had a marked correlation with sustained remission for 2 years, and the former cut off value, 1.97 of DAS28-ESR (specificity:73%, sensitivity:77%) was same as for 1 year sustaining remission [ref.1]. In patients with the deep remission (DAS28-ESR <1.97) at the study entry of ADA-free, the clinical remission rates 2 years after ADA discontinuation (62%) was similar as 1 year after ADA discontinuation (68%). The latter cut off value, age 56 (specificity:83%, sensitivity:71%) was newly identified in this analysis. In patients of age under 56, the clinical remission rate (71%) 2-years after ADA-free was as high as that of ADA continuation group. No change was observed in the proportion of functional remission (HAQ-DI ≤0.5) in patients who sustained low disease activity during ADA-free, that is, the functional remission rates were 94% both 1-year and 2-years after ADA discontinuation, and no significant difference was observed between ADA discontinuation and continuation groups. Conclusions: A new prognostic factor, age (<56) was identified to sustain clinical remission for 2 years in addition to the deep remission (DAS28<1.97), and the HONOR study demonstrated that ADA can be discontinued at least for 2 years in some patients, showing as high clinical remission rates as that of ADA continuation group (67%) 2 year after study entry, that is, 62% in patients with deep remission (DAS28-ESR<1.97) or 71% in patients under age 56, and also no functional damage in patients with DAS28-ESR<3.2 during ADA-free. References: Tanaka Y, et al. Ann Rheum Dis 2013; 0:1-7. doi:10.1136/annrheumdis-2013-204016 Acknowledgements: The author thanks all medical staff of the HONOR group and at all institutions for providing the data. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4002